Impact of water table fluctuations on the seasonal effectiveness of the pump-and-treat remediation in wet–dry tropical regions - Teramoto, Elias Hideo [UNESP]; Pede, Marco Aurélio Zequim [UNESP]; Chang, Hung Kiang [UNESP] (Springer Nature, 2020)
The pump-and-treat (P&T) method is a common remediation approach that is used to mitigate occurrences of hydrocarbon contamination. In a well-studied site that had been contaminated by a large volume of jet fuel, continuous monitoring of the water table and floating phase thickness revealed the most significant process governing the effectiveness of the site’s active remediation system. The floating phase thickness recorded in the wells monitored varied greatly (> 0.50 m) and was negatively correlated with the water table level. Although the dependence of light non-aqueous phase liquid (LNAPL) thickness on water table fluctuations is widely recognized, LNAPL recovery, which is governed by alternating cycles of LNAPL release and entrapment in pore spaces, has been poorly described. Thus, we present a specific case in which LNAPL recovery is expected only episodically, when the water table falls sufficiently. In the period spanning from 2006 to 2008, LNAPL remediation recovered nearly 180 m3 of oil. In later years, the volume of recovered LNAPL declined and ceased between 2010 and 2014, when the water table rose. Importantly, our research demonstrates that the P&T remediation approach is solely effective during a period of 4 months in dry years. Thus, cleanup methods and contaminated site management strategies should be reconsidered.
Keywords: Hydrocarbon contamination; Hydrology of tropical climates; LNAPL entrapment; LNAPL remediation; Pump-and-treat; Water table fluctuation